Association of Knowledge and Attitude Toward Antibiotic Use and Resistance With Self‐Medication Practice of Antibiotics Among Bangladeshi Private University Teachers: A Cross‐Sectional Study - Safayet Jamil; Md. Jamal Hossain; Habib Mohammad Ali; Md. Rakib Akon; Mubarick Nungbaso Asumah; Mahdi Hasan; Harshini Suresh; Olalekan John Okesanya; Md. Al‐Mamun; Mohamed Mustaf Ahmed; Tanzeema Younus Sarkar; Md. Fouad Hossain Sarker (Health Science Reports)
ABSTRACT Background and Aims Antibiotic resistance is increasing globally and regionally, posing a significant public health concern. This study aimed to assess knowledge and attitude toward antibiotic use and the prevalence of self‐medication and its association with the knowledge and attitude toward antibiotic use and resistance among private university teachers in Bangladesh. Methods This quantitative, cross‐sectional study utilized a convenience sampling technique and included 509 respondents. All data were collected using both face‐to‐face and online versions. Data were collected through both face‐to‐face and online surveys with all questions in a closed‐ended format. Data analysis was conducted using IBM SPSS (version 20), employing frequency analysis, chi‐squared tests, and logistic regression. Results Among the respondents, 47.9% demonstrated high knowledge of antibiotic use and resistance. Only 19.3% showed a strong positive attitude toward antibiotic use and resistance. Self‐medication with antibiotics was reported by 29.0% of respondents. Logistic regression analysis revealed that female participants were 5.02 times more knowledgeable about antibiotic use and resistance than male participants (95% CI: 2.72−9.91; p < 0.001). Additionally, respondents over 40 years old had a 3.71 times higher attitude toward antibiotic use and resistance than those aged 30 or below (95% CI: 1.98−7.06; p < 0.001). Females were 6.79 times more likely to self‐medicate with antibiotics compared to males (95% CI: 3.67−13.43), and respondents aged 31−40 were 3.91 times more likely to practice self‐medication than other age groups (95% CI: 1.07−3.86). Furthermore, participants with low knowledge and a low attitude toward antibiotic use and resistance were 3.87 times and 4.26 times more likely to self‐meditate, respectively, than those who had high knowledge and attitude scores (95% CI: 2.00−5.70 and 95% CI: 1.99−5.12). Conclusion To combat antibiotic resistance, campaigns and seminars on responsible antibiotic use should be held at university level. Additionally, enforcement of laws prohibiting unnecessary antibiotic sales in retail pharmacies is essential.